Mk3 kiln built with construction and demolition waste to mitigate pm2.5 and pm10 in the production of handmade bricks in Peru - Contreras Perez, Alex Hugo (2024)
The study focuses on the design of the MK3 kiln as an eco-friendly solution to mitigate the pollution of (PM2.5 and PM10) generated by artisanal brick kilns. The MK3 kiln consists of three chambers constructed with construction and demolition waste (CDW), interconnected by lower ducts that aid in the continuous flow of heat and filter pollutants. Each kiln has a 5 cm opening in the dome to accommodate a copper industrial torch with a power of 1080 BTU/h, equivalent to 0.32 kW. Additionally, a 220V axial fan is installed in the chimney to supply the necessary air to the kilns through upper ducts, allowing complete combustion during the brick baking process. As a result, PM2.5 was measured at a quantity of 23 μg/m 3 , and PM10 emissions at 90 μg/m 3 , both of which do not exceed Environmental Quality Standards (ECA). Regarding the brick baking process, heat is recovered from the "combustion kiln" to the "recovery kiln," reaching a temperature of 70.8 °C through the cogeneration system. Furthermore, the brick baking process reaches a temperature of 746.3 °C over a period of 4 hours (240 minutes), ensuring high levels of strength. Finally, the energy of the combustion process is continuously optimized, presenting an efficient alternative by using propane gas as fuel, which is versatile for brick baking.